Generation, characterization, and drug sensitivities of 12 patient-derived IDH1-mutant glioma cell cultures. Issue 1 (2nd August 2021) - Verheul, Cassandra; Ntafoulis, Ioannis; Kers, Trisha V; Hoogstrate, Youri; Mastroberardino, Pier G; Barnhoorn, Sander; Payán-Gómez, César; Tching Chi Yen, Romain; Struys, Eduard A; Koolen, Stijn L W; Dirven, Clemens M F; Leenstra, Sieger; et al.
Abstract: Background: Mutations of the isocitrate dehydrogenase ( IDH ) gene occur in over 80% of low-grade gliomas and secondary glioblastomas. Despite considerable efforts, endogenous in vitro IDH -mutated glioma models remain scarce. Availability of these models is key for the development of new therapeutic interventions. Methods: Cell cultures were established from fresh tumor material and expanded in serum-free culture media. D-2-Hydroxyglutarate levels were determined by mass spectrometry. Genomic and transcriptomic profiling were carried out on the Illumina Novaseq platform, methylation profiling was performed with the Infinium MethylationEpic BeadChip array. Mitochondrial respiration was measured with the Seahorse XF24 Analyzer. Drug screens were performed with an NIH FDA-approved anti-cancer drug set and two IDH-mutant specific inhibitors. Results: A set of twelve patient-derived IDHmt cell cultures was established. We confirmed high concordance in driver mutations, copy numbers and methylation profiles between the tumors and derived cultures. Homozygous deletion of CDKN2A/B was observed in all cultures. IDH-mutant cultures had lower mitochondrial reserve capacity. IDH-mutant specific inhibitors did not affect cell viability or global gene expression. Screening of 107 FDA-approved anti-cancer drugs identified nine compounds with potent activity against IDHmt gliomas, including three compounds with favorable pharmacokinetic characteristics for CNS penetration: teniposide, omacetaxine mepesuccinate, and marizomib. Conclusions: Our twelve IDH-mutant cell cultures show high similarity to the parental tissues and offer a unique tool to study the biology and drug sensitivities of high-grade IDHmt gliomas in vitro . Our drug screening studies reveal lack of sensitivity to IDHmt inhibitors, but sensitivity to a set of nine available anti-cancer agents.